Implementasi Peraturan Daerah No. 1 Tahun 2017 Kota Parepare tentang Pajak Restoran (Perspektif Hukum Ekonomi Islam) - rahman, faidah (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2023)
Regional governments have the authority and independence to regulate regional government affairs. Each region in carrying out government affairs under its authority has the right to make policies both in the context of improving services and in the context of increasing community participation in regional development. One of the important components in implementing the process is through the establishment of regional regulations. The purpose of this study was to determine the implementation of regional regulations on restaurant taxes and regional income through restaurant taxes from the perspective of sharia economic law. The research method used is qualitative, this research study uses a qualitative descriptive analysis technique with a data analysis model approach. The conclusion of this study is that the existence of a local restaurant tax regulation makes it easier for business actors to pay compared to before there was a regional regulation because it is no longer business actors who are charged with paying taxes but consumers pay taxes according to what has been regulated and the mayor and Regional Revenue of Parepare City through restaurant taxes from an Economic Law perspective Sharia in Parepare City is used to help the community and regional development with a total contribution of 2.75% in the last 4 years.